Hypergammaglobulinemia D and Periodic Fever Syndrome (HIDS) in a 3-year-old Patient from Puerto Rico - Alicea-Negrón, Abdiel J.; Toledo-García, Marilyn; Torres-Quiñones, Marta; López-Martínez, Annette; González-Chávez, Jose R. (Puerto Rico Health Sciences Journal, 2024)
Mevalonate kinase deficiency is a rare autosomal recessive disease caused by mutations in the mevalonate kinase gene (MVK). Depending on the mutations, a patient with this deficiency can exhibit any one of a spectrum of rare autoinflammatory diseases, such as hypergammaglobulinemia D (hyper-IgD) with periodic fever syndrome and mevalonic aciduria. To date, approximately 300 cases with mutations in the MVK gene have been reported worldwide. Herein, we present a 3-year-old female from Puerto Rico with a history of fever, arthralgia, and skin lesions since her first month of age and who, upon genetic workup, was confirmed to have compound heterozygous mutations in the MVK gene. Given her medical history and the results of her genetic testing, she was diagnosed with hyper-IgD with periodic fever syndrome. She will be treated with canakinumab, an interleukin-1ß antagonist, after receiving the varicella and measles–mumps–rubella (MMR) vaccines.